Efqm mükemmellik modelinde bir araç olarak öğrenen organizasyonlar felsefesi - Birsel, Birnur (My University, 2002)
Bu çalışma modern yönetim ve organizasyon modellerinden olan EFQM Mükemmellik Modeli ve Öğrenen organizasyonlar felsefesini inceleyerek, EFQM Mükemmellik Modeli içerisinde öğrenen organizasyon felsefesinin rolünü ortaya koymaya çalışmaktadır. 21. Yüzyılın beraberinde getirdiği değişim rüzgarları, organizasyonların ağır rekabet şartları altında var olma savaşı vermelerine neden olmuştur. Bilginin değeri iyice anlaşılmış ve bilgiye sahip olup, bilgi birikimini arttırabilen organizasyonlar ön plana çıkmıştır. Bu gelişmeler ışığında çalışanların ve onun bilgi birikiminin değeri anlaşılarak, bu bilgiyi organizasyon içinde yayabilen yönetim modellerinin önemi artmıştır. 1980'li yıllarda Avrupa oldukça düşük fiyatlarla en yüksek kalitede ürün sunan Asyalı rakiplerinin yarattığı baskıyı hissetmeye başladı. Bu durum karşısında 1988 yılında Avrupa'nın önde gelen 14 şirketi kendilerinin başarıya götürecek bir yönetim ve organizasyon modeli oluşturmak için bir araya gelerek Avrupa Kalite Yönetim Vakfı (European Foundation For Quality Management)'nı kurmuşlardır. Bu gün üye sayısı 800'e ulaşan EFQM, üyelerinden gelen geri bildirimi değerlendirerek Mükemmellik Modelini sürekli yeniler. EFQM Mükemmellik Modelinin başarılı olmasının sağlayan temel faktör ise, öğrenmedir. Çevresindeki değişimlere duyarlı ve esnek olmayı başarmak için bir organizasyonun öğrenen bir organizasyon haline gelmesi gerekir. Bunun farkında olana EFQM öğrenmeyi modelin merkezine oturtmuştur.

This study aims to reveal, by investigating the EFQM (European Foundation for Quality Management) Excellence Model ness and the Philosophy of Learning Organizations of which is one of the modern management and organization models, the role of the philosophy of learning organization in the EFQM Excellence Model ness. The wind of change, which 21st Century has brought, has caused the organizations to battle for surviving under heavy conditions of competition. The value of information has been recognized, and the organizations which had this information and increased their accumulation of information have come to the fore. Under the light of these developments, the value of the workers and the accumulation of information thereof have been recognized, the popularity of the management models which was capable to spread this information in the entire organization has increased. In 1980s, Europe began to feel the stress of its Asian competitors supplying the products of the highest quality with reasonably cheap prices. After this circumstance, 14 European leading companies gathered in 1988, in order to form a management and organization model which would lead them to success, and founded the European Foundation for Quality Management. EFQM, which the members there of have reached 800, renews, by assessing the information coming from its members, its Excellence Model ness continuously. The main factor which makes the EFQM Excellence Model ness successful is learning. It is essential an organization to be a learning organization in order to achieve being sensitive and flexible against the variations in the surroundings. EFQM which is aware of this fact has placed the learning to the center of the model. EFQM awards its members, which have caught the perfect ness in organization, with European Quality Award each year. This makes the companies gain a great prestige. In the 21st Century which is named as the age of information, the successful companies shall be those which have achieved to establish the rapid learning in every department of their organizations
Keywords: Çalışma Ekonomisi; Genel yönetim; Organizasyon; Üretim yönetimi; Yönetim Ve Organizasyon